A Cycle of State-Building: The Process of Growth in the Yishuv During the Fifth Aliyah. - Lloyd-Thomas, Sophia C. (Tufts University. Tisch Library., 2018)
Tisch Library Undergraduate Research Award Winner, 2018. The period of Jewish immigration to British Mandatory Palestine from 1929-1939, better remembered as the Fifth Aliyah, transformed the Yishuv from a rudimentary political unit into a proto-state ready for independence. A perfect storm of converging external factors informing internal operations created a feedback cycle that enabled this dramatic development. This cycle begins with Jewish immigration fed by the growing attractiveness of life in the Yishuv compared to the Diaspora. This growth then informs Arab opposition, British policy, and finally Zionist state-building endeavors that further immigration efforts and start the cycle all over again. The complete cycle occurs twice in the period of the Fifth Aliyah, intensifying in its second iteration. This paper seeks to explore this pattern as a major cause of development and eventual independence of the Jewish proto-state.